International variation in rates of uptake of preventive options in BRCA1 and BRCA2 mutation carriers - Metcalfe, Kelly A.; Birenbaum‐Carmeli, Daphna; Lubinski, Jan; Gronwald, Jacek; Lynch, Henry; Moller, Pal; Ghadirian, Parviz; Foulkes, William D.; Klijn, Jan; Friedman, Eitan; Kim‐Sing, Charmaine; Ainsworth, Peter; et al. (International journal of cancer, 2008)
Several options for cancer prevention are available for women with a BRCA1 or BRCA2 mutation, including prophylactic surgery, chemoprevention and screening. The authors report on preventive practices in women with mutations from 9 countries and examine differences in uptake according to country. Women with a BRCA1 or BRCA2 mutation were contacted after receiving their genetic test result and were questioned regarding their preventive practices. Information was recorded on prophylactic mastectomy, prophylactic oophorectomy, use of tamoxifen and screening (MRI and mammography). Two thousand six hundred seventy‐seven women with a BRCA1 or BRCA2 mutation from 9 countries were included. The follow‐up questionnaire was completed a mean of 3.9 years (range 1.5–10.3 years) after genetic testing. One thousand five hundred thirty‐one women (57.2%) had a bilateral prophylactic oophorectomy. Of the 1,383 women without breast cancer, 248 (18.0%) had had a prophylactic bilateral mastectomy. Among those who did not have a prophylactic mastectomy, only 76 women (5.5%) took tamoxifen and 40 women (2.9%) took raloxifene for breast cancer prevention. Approximately one‐half of the women at risk for breast cancer had taken no preventive option, relying solely on screening. There were large differences in the uptake of the different preventive options by country of residence. Prophylactic oophorectomy is now generally accepted by women and their physicians as a cancer preventive measure. However, only the minority of women with a BRCA1 or BRCA2 mutation opt for prophylactic mastectomy or take tamoxifen for the prevention of hereditary breast cancer. Approximately one‐half of women at risk for breast cancer rely on screening alone. © 2008 Wiley‐Liss, Inc.